Synthesis AuNPs Using Moringa oleifera Extract and Potential Study as Colorimetric Microplastic Detection - Thohir, Muhammad Bakhru; Setyaningrum, Dyah; Efendi, Meilisa Rusdiana Surya; Saputra, Arya Ananda; Nursaida, Marta Citra (Universitas Pendidikan Mandalika, 2025)
Nanoparticles are multipurpose materials that have been utilized in the medical, energy, and environmental monitoring fields. The advantage of nanoparticles is that they have unique physicochemical properties such as surface area, optical activity, and surface modifiability. One of the important uses of nanoparticles is for environmental monitoring. This is because the surface of nanoparticles can be modified, and with their small size, they can reach analytes in difficult matrices. However, conventional synthesis methods of nanoparticles have been unsustainable. Therefore, the synthesis of AuNPs using bioreductors was considered urgent. The aim of this research was to determine the optimum conditions for the synthesis of AuNPs with Moringa oleifera (MO) as a bioreductor to obtain AuNPs-MO, to characterize the synthesized AuNPs-MO, and to study the application of AuNPs-MO for monitoring microplastic pollutants. This research was conducted through the stages of extraction, determination of optimum conditions, characterization, and literature study of the potential of AuNPs-MO as a detector. Determination of optimum conditions was carried out by applying variations in pH and precursor-reducing agent ratio. The optimal pH was found to be 6, and the optimal volume ratio was 15:5 (mL). Characterization of AuNPs-MO was conducted using FTIR and PSA. The FTIR spectra showed identical absorption patterns for AuNPs synthesized with bioreductants, and the particle size was found to be 61.15 nm. In addition, microplastics were detected using AuNPs both directly, through surface modification with proteins, and indirectly, with the assistance of acetone. From this series of experiments, satisfactory results were obtained.